Cellular Stress Responses: Cell Survival and Cell Death. (29th December 2009) - Fulda, Simone; Gorman, Adrienne M.; Hori, Osamu; Samali, Afshin
Abstract : Cells can respond to stress in various ways ranging from the activation of survival pathways to the initiation of cell death that eventually eliminates damaged cells. Whether cells mount a protective or destructive stress response depends to a large extent on the nature and duration of the stress as well as the cell type. Also, there is often the interplay between these responses that ultimately determines the fate of the stressed cell. The mechanism by which a cell dies (i.e., apoptosis, necrosis, pyroptosis, or autophagic cell death) depends on various exogenous factors as well as the cell's ability to handle the stress to which it is exposed. The implications of cellular stress responses to human physiology and diseases are manifold and will be discussed in this review in the context of some major world health issues such as diabetes, Parkinson's disease, myocardial infarction, and cancer.